2022
DOI: 10.1002/hbm.26062
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐specific microstructural patterns of anterior hippocampus in Alzheimer's disease with ex vivo diffusion MRI at 14.1 T

Abstract: High‐resolution ex vivo diffusion MRI (dMRI) can provide exquisite mesoscopic details and microstructural information of the human brain. Microstructural pattern of the anterior part of human hippocampus, however, has not been well elucidated with ex vivo dMRI, either in normal or disease conditions. The present study collected high‐resolution (0.1 mm isotropic) dMRI of post‐mortem anterior hippocampal tissues from four Alzheimer's diseases (AD), three primary age‐related tauopathy (PART), and three healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…[ 66 , 67 ] For instance, the 14 T MRI has been utilized to study structural changes in the hippocampus of human brains with Alzheimer's disease. [ 68 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 66 , 67 ] For instance, the 14 T MRI has been utilized to study structural changes in the hippocampus of human brains with Alzheimer's disease. [ 68 ]…”
Section: Discussionmentioning
confidence: 99%
“…[66,67] For instance, the 14 T MRI has been utilized to study structural changes in the hippocampus of human brains with Alzheimer's disease. [68] On the other hand, there are several limitations of ultrahigh field MRI. First, ultrahigh magnetic field MRI (>7 T) has not been approved in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…An recent ex-vivo human brain study in AD using T2-weighted MRI found signi cant relationships between phosphorylated tau and cortical thickness in primary visual cortices, temporal pole, insular cortex, and posterior cingulate gyri[62]. Our previous ex-vivo studies in the human hippocampus revealed signi cant correlations between magnetic susceptibility and Aβ/Tau content in AD and PART, as well as between dMRI measurements and Aβ/Tau content in AD[25, 63]. These ndings indicate that changes in MRI could re ect the effects of Aβ or Tau or both on the brain.…”
mentioning
confidence: 85%
“…More importantly, ex-vivo MRI enables direct MRI-histology correlation of the same human brain. Our recent studies found layer-speci c microstructural changes in the hippocampus that signi cantly correlated with Aβ/Tau protein content in AD samples [25]. However, the aforementioned ex-vivo dMRI studies all focused on speci c small tissue blocks and did not characterize how layerspeci c Aβ/Tau deposition affects the cortical microstructure across the whole hemisphere.…”
Section: Introductionmentioning
confidence: 97%
“…43 From these DTI data, fractional anisotropy (FA) values were calculated as a measure of the directionality and coherence of water molecule diffusion within the white matter tracts. 44 FA is a widely used scalar metric derived from the diffusion tensor, which provides valuable insights into the microstructural organization and integrity of white matter fibers. 45 Lower FA values are generally associated with disruptions or disorganization of white matter pathways, which can occur in various neurological conditions, including dementia.…”
Section: Methodsmentioning
confidence: 99%